The Impact of Sustainability Reporting and Corporate Social Responsibility Implementation on Financial Performance with Corporate Governance as an Intervening Variable in Infrastructure Sector Companies on the Indonesia Stock Exchange in 2021–2024 - Moulinda Dora; Andri Zainal; Azizul Kholis (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study analyzes the Effect of the Implementation of Sustainability Reporting and Corporate Social Responsibility on Financial Performance with Corporate Governance as an Intervening Variable in Infrastructure Sector Companies on the Indonesia Stock Exchange in 2021-2024. The research sample is infrastructure companies listed on the IDX for the 2021-2024 period, totaling 45 companies with 180 observations. The data analysis technique uses panel data regression equations with path analysis. This study obtains several empirical evidences, namely, first, sustainability reporting directly has a negative and significant effect on financial performance. Second, corporate social responsibility directly provides a positive and significant influence on financial performance. This result can be interpreted based on stakeholder theory that companies that pay attention to CSR disclosure and already have corporate social responsibility reporting standards can increase stakeholder trust. Third, corporate governance does not moderate the relationship between sustainability reporting and financial performance. A large percentage of management ownership, and it is estimated that there will be an increase in management performance by creating innovation, new ideas obtained from employee resource skills and knowledge, and managerial ownership follows its control rights more than alignment of interests. Fourth, corporate governance moderates the influence of corporate social responsibility on financial performance. The results of this study are based on resource-based theory, that the existence of concern for the environment owned by the company is supported by the company's good intellectual ability, proving that the company is able to manage its intellectual resources effectively and efficiently, and indicates increasingly high financial performance and gets a positive response from investors.